Antecedents of visitors' revisit intention to Bank Indonesia Library in Surabaya - Nabila, Ilsa; Wahdah, Nikmatul Bahril; Suharto, Bambang; Isnaini, Santi (Universitas Padjadjaran, 2024)
The Bank Indonesia Library in Surabaya acts as a manager of knowledge and education for the community. When visiting the Bank Indonesia Library in Surabaya, users will notice the quality of space and public services. Library services are an attraction for users to visit. This study aims to determine the factors that cause antecedents of visitor’s intention to revisit the Bank Indonesia Library in Surabaya through an analysis of the relationship between visitor happiness, public services, quality of public space, and the intention to return to the library. The research method uses a quantitative approach with a descriptive correlational design in the form of a questionnaire distributed directly and indirectly to library visitors. The results showed that the quality of public space significantly and positively affected visitor satisfaction, confirming the importance of public space in improving user experience. However, the quality of public services did not show a significant effect on visitor satisfaction, indicating the presence of other more dominant factors. In addition, both the quality of public space and public services did not have a significant indirect effect on intention to revisit when mediated by visitor satisfaction. Improving the quality of public space is important so that service quality can influence visitor behavior. This study concludes that the quality of public space is a major factor in visitor satisfaction, while public services require further improvement to increase their contribution to satisfaction and intention to revisit.